Ketersediaan Pangan Pokok Pada Rumah Tangga Petani Di Wilayah Terpencil - Ayu Marshya; A Amrullah; Nurbaya Busthanul (Jurnal Sosial Ekonomi Pertanian, 2023)
Abstract Indonesia is known as an agricultural country, but currently Indonesia often imports food from other countries to meet the food needs of its people. The food need in question is the need for staple food (rice). This study aims to determine the availability of staple food of farmer households in Sumabu Village. The basic method in this research is descriptive analytical with the implementation using survey techniques. The research location was chosen purposively, in Sumabu Village. The determination of the sample farmers was carried out using the Slovin formula so as to produce 55 respondent farmers. The data used are primary data and secondary data. The data analysis used is the analysis of the availability of staple food. The results showed that the average availability of staple food in farmer households in Sumabu Village was 1,552.36 kcal/cap/day which was in the medium category.